1994
DOI: 10.1093/bja/73.2.244
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nabilone on nausea and vomiting after total abdominal hysterectomy

Abstract: In a prospective, double-blind study, we have examined the effect of preoperative nabilone on postoperative nausea and vomiting (PONV). Sixty women, less than 70 yr old, undergoing total abdominal hysterectomy, were allocated randomly to receive either nabilone 2 mg or metoclopramide 10 mg orally 90 min before induction of anaesthesia. The study was designed to detect a 50% difference in the incidence of postoperative vomiting between the two groups, with an 80% power of achieving a statistically significant r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 4 publications
0
14
0
2
Order By: Relevance
“…The antiemetic effect of the oral cannabinoid nabilone on nausea and vomiting was investigated in a single randomized study including 60 women undergoing total abdominal hysterectomy [6]. The study, which was published in 1994, showed a tendency towards a lower incidence of postoperative vomiting after the application of 2 mg nabilone compared with 10 mg metoclopramide.…”
Section: The Role Of the Endocannabinoid System In Anaesthesiamentioning
confidence: 99%
“…The antiemetic effect of the oral cannabinoid nabilone on nausea and vomiting was investigated in a single randomized study including 60 women undergoing total abdominal hysterectomy [6]. The study, which was published in 1994, showed a tendency towards a lower incidence of postoperative vomiting after the application of 2 mg nabilone compared with 10 mg metoclopramide.…”
Section: The Role Of the Endocannabinoid System In Anaesthesiamentioning
confidence: 99%
“…Although their precise mechanism of preventing PONV is unknown, their effects are thought to be mediated by the drug class's antiinflammatory or membranestabilizing activities peripherally or centrally. 10 Cannabinoids have been demonstrated to be effective and hold promise for a role in treating CINV; however, the literature does not support their use for PONV, 26 …”
Section: Overview Of Antiemetic Agents Currently In Usementioning
confidence: 99%
“…In einer randomisierten, doppelblinden Studie wurden 2 mg Nabilone mit 10 mg Metoclopramid zur Verhinderung von postoperativer Übelkeit und Erbrechen bei 53 Frauen nach abdomineller Hysterektomie verglichen [21]. Die Medikamente wurden 90 min vor der Einleitung der Anästhesie verabreicht.…”
Section: Cannabinoide Bei Postoperativer üBelkeit Und Erbrechenunclassified